The Boundaries of the Role of Women in Political Life - Flynn, Erin (Maine Policy Review, 2008)
Each year, the Margaret Chase Smith Library sponsors an essay contest for Maine high school seniors. We feature here Erin Flynn’s 2008 first place prize-winning essay. Students were asked to assess whether the ideals of the 19th Amendment, granting voting rights to women, have been fulfilled and to discuss the social and cultural barriers remaining for women to overcome in the pursuit of political power, long after legal barriers to equal participation have been removed.